Nonsteroidal anti‐inflammatory drugs and other analgesic use and bladder cancer in northern New England 1. Issue 1 (22nd May 2012) - Baris, Dalsu; Karagas, Margaret R.; Koutros, Stella; Colt, Joanne S.; Johnson, Alison; Schwenn, Molly; Fischer, Alexander H.; Figueroa, Jonine D.; Berndt, Sonja I.; Han, Summer; Beane Freeman, Laura E.; Lubin, Jay H.; et al.
Abstract A few epidemiologic studies have found that use of nonsteroidal anti‐inflammatory drugs (NSAIDs) is associated with reduced risk of bladder cancer. However, the effects of specific NSAID use and individual variability in risk have not been well studied. We examined the association between NSAIDs use and bladder cancer risk, and its modification by 39 candidate genes related to NSAID metabolism. A population‐based case–control study was conducted in northern New England, enrolling 1, 171 newly diagnosed cases and 1, 418 controls. Regular use of nonaspirin, nonselective NSAIDs was associated with reduced bladder cancer risk, with a statistically significant inverse trend in risk with duration of use (ORs of 1.0, 0.8, 0.6 and 0.6 for <5, 5–9, 10–19 and 20+ years, respectively; ptrend = 0.015). This association was driven mainly by ibuprofen; significant inverse trends in risk with increasing duration and dose of ibuprofen were observed (ptrend = 0.009 and 0.054, respectively). The reduced risk from ibuprofen use was limited to individuals carrying the T allele of a single nucleotide polymorphism (rs4646450) compared to those who did not use ibuprofen and did not carry the T allele in the CYP3A locus, providing new evidence that this association might be modified by polymorphisms in genes that metabolize ibuprofen. Significant positive trends in risk with increasing duration and cumulative dose of selective cyclooxygenase (COX‐2) inhibitors were observed. Our results are consistent with those from previous studies linking use of NSAIDs, particularly ibuprofen, with reduced risk. We observed a previously unrecognized risk associated with use of COX‐2 inhibitors, which merits further evaluation.